2015
DOI: 10.7448/ias.18.2.19393
|View full text |Cite
|
Sign up to set email alerts
|

Review: An urgent need for research on factors impacting adherence to and retention in care among HIV‐positive youth and adolescents from key populations

Abstract: IntroductionThe 50% increase in HIV-related deaths in youth and adolescents (aged 10–24) from 2005 to 2012 highlights the need to improve HIV treatment and care in this population, including treatment adherence and retention. Youth and adolescents from key populations or young key populations (YKP) in particular are highly stigmatized and may face additional barrier(s) in adhering to HIV treatment and services. We reviewed the current knowledge on treatment adherence and retention in HIV care among YKP to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 43 publications
4
107
0
Order By: Relevance
“…The increased risk of virological failure among older adolescents could be explained by the developmental milestones gone through by older adolescents in transition to their adulthood as compared to the younger adolescents. These include social, emotional and cognitive changes [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of virological failure among older adolescents could be explained by the developmental milestones gone through by older adolescents in transition to their adulthood as compared to the younger adolescents. These include social, emotional and cognitive changes [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Technology-enabled interventions for adherence support have only recently been tested in HIV-infected adolescents and young adults, and although promising, synthesis of the findings from the nine identified primary studies reflects a paucity of published peer-reviewed evidence in the US during the past decade. In fact, the evidence base for adherence interventions and recent trends of intervention research are disproportionate to the needs of this population [23, 35, 36]. Hence, the ability to generate broad recommendations from this review is limited.…”
Section: Discussionmentioning
confidence: 99%
“…To date, technology-enabled interventions have shown promise for a range of chronic conditions [15], including HIV-in-fected adolescent, young adult, and adult cohorts from domestic and international settings [1621]. However, much less is known about the impact of health technology-enabled interventions on the HIV care cascade [22] with significant knowledge gaps in research targeting ART adherence and retention outcomes among HIV-infected youth [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Our research has identified an overall lack of rigorous adherence enhancing research, which has been echoed in a number of recent research syntheses. [5,23] Evidence for effective interventions for YLWH failing ART regimens is even less well represented in the literature. Although agencies and service providers are advised to adopt evidence-based adherence support strategies, there are no strong, rigorously tested interventions to consider.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Furthermore, evidence suggests using phone-based technology to engage adolescent social support networks may promote optimal engagement in care and adherence to medications. [22,23] A recent study of a phone-based support intervention among nonadherent YLWH found that it was acceptable and feasible among youth and clinic staff. [24] Coaching at clinic visit.…”
Section: Outreach Between Clinic Visitsmentioning
confidence: 99%